Fierce Elegy - Gizzi, Peter (Book collections on Project MUSE., 2023)
"Peter Gizzi's powerful new collection reminds us that the elegy is lament but also-as it has been for centuries-a work of lovePeter Gizzi has said that "the elegy is a mode that can transform a broken heart in a fierce world into a fierce heart in a broken world." For Gizzi, ferocity can be reimagined as vulnerability, bravery and discovery, a braiding of emotional and otherworldly depth, "a holding open." In Gizzi's voice joy and sorrow make a complex ecosystem. In their quest for a lyric reality, these poems remind us that elegy is lament but also-as it has been for centuries-a work of love. "This new poetry," Kamau Brathwaite has written about Gizzi, "taking such care of temperature-the time & details of the world-meaning the space(s) in which we live-defining love in this way. Writing along the edge. A way of writing about hope." [sample poem] Creely Song all that is lovely in words, even if gone to pieces all that is lovely gone, all of it for love and autobiography as if I were writing thishello, listen the plan is the body and all of it for love now in pieces all that is lovely echoes still in life & death still memory gardens open onto windows lovely, the charm that mirrors all that was, all that is, lovely in a song"--